PENGARUH NILAI HUMANIS BUDDHA DAN POLA PIKIR MELALUI MEDIASI EFIKASI DIRI TERHADAP KOMITMEN GURU TZU CHI - Hang Jung Jung; Lianah The; Sulan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of modern education requires teachers to possess professional competence, humanistic character, and a positive mindset to enhance their commitment in carrying out their duties. This study aims to analyze the influence of Buddhist Humanistic Values and Mindset on Teacher Commitment, with Self-Efficacy as a mediating variable. The research employed a quantitative approach using a census method involving 200 elementary school teachers at Tzu Chi School in Jakarta. Data were collected through questionnaires, observations, and documentation, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that the model explains 45.6% of Self-Efficacy and 46.7% of Teacher Commitment. Buddhist Humanistic Values have a positive and significant effect on both Self-Efficacy and Teacher Commitment. Similarly, Mindset also has a positive and significant influence on both Self-Efficacy and Teacher Commitment. In addition, Self-Efficacy has a positive and significant effect on Teacher Commitment. The mediation analysis indicates that Self-Efficacy partially mediates the effect of Mindset on Teacher Commitment, but does not mediate the effect of Buddhist Humanistic Values on Teacher Commitment. This study concludes that teacher commitment is formed through two main pathways. Buddhist Humanistic Values directly strengthen teachers’ emotional attachment and loyalty to their profession, while Mindset enhances commitment indirectly by increasing Self-Efficacy. Therefore, human resource development in Tzu Chi schools should integrate the strengthening of humanistic values with the creation of a psychologically safe work environment to improve teachers’ confidence and professional commitment.